Extraction and Characterization of Moringa Seed Oil Results from Soxhletation and Screw Pressing - Handayani, Sri Seno; Gunawan, Erin Ryantin; Suhendra, Dedy; Murniati, Murniati; Bali, Rizka Dhia Khalilah; Sari, Gita Sagita (Jurnal Pijar Mipa, 2025)
Moringa seed oil is a vegetable oil that has many benefits for health and the pharmaceutical industry. Moringa seed oil can be extracted either chemically or mechanically. This research aims to characterize moringa seed oil’s physicochemical properties and fatty acid composition using soxhletation chemical extraction and screw-pressing mechanical extraction with various pretreatment temperatures of 50, 60, and 70°C. The research showed that the highest yield of moringa seed oil, 41.74%, was obtained at an initial treatment temperature of 70°C using the soxhletation method for 6 hours. The acid value of moringa seed oil from soxhletation is 2.01 mg KOH/g, and screw pressing is 4.37 mg KOH/g. The iodine number from soxhletation was 66.62 mg iod/100g, and screw pressing was 60.27 mg iod/100g. The density of the oil from soxhletation and screw pressing is 0.922 mg/mL and 0.934 mg/mL, respectively, with an oil viscosity of 3.298 cP and 3.424 cP. The results of GC-MS analysis show that moringa seed oil from soxhletation has an oleic acid composition of 40.92%, while the screw pressing has an oleic acid composition of 22.50%. This finding demonstrates the influence of extraction methods on the fatty acid profile, particularly the concentration of oleic acid, a key component of moringa seed oil. These results contribute to understanding how specific extraction techniques can optimize the quality of moringa seed oil.